Designing and constructing prestressed bridges - Stránský, Jiří; Nečas, Radim (ICE Publishing, 2021)
Designing and Constructing Prestressed Bridges shows how designs using prestressing methods can be utilised in the building of bridge structures. Prestressed bridges can be used in a variety of locations and styles and it can often be difficult to understand the intricacies of the design. This book solves this concern by discussing the aspects of bridge design in order to find the most appropriate solution. The book focuses on troubleshooting the problems that are connected with finding the correct structural solution of bridges, the methods of their construction and the corresponding arrangement of prestressing steel.